Disability Studies and Spanish Culture Films, Novels, the Comic and the Public Exhibition - Fraser, Benjamin (Representations: Health, Disability, Culture and Society, 2013)
Disability Studies and Spanish Culture is the first book to apply the tenets of Disability Studies to the Spanish context. In particular, this work is an important corrective to existing cultural studies of disability in Spain that tend to largely ignore intellectual disabilities. Taking on the representation of Down syndrome, autism, alexia/agnosia as well as childhood disability, its chapters combine close readings of a number of Spanish cultural products (films, novels, the comic/graphic novel and the public exhibition) with a broader socio-cultural take on the state of disability in Spain. While researchers and students of cinema will be particularly interested in the book's detailed analyses of the formal aspects of the films, comics, and novels discussed, readers from backgrounds in history, political science and sociology will all be able to appreciate discussions of contemporary legislation, advocacy groups, cultural perceptions, models of social integration and more.